A massively scalable Time-to-Digital Converter with a PLL-free calibration system in a commercial 130 nm process. (17th November 2021) - Martinelli, F.; Valerio, P.; Cardarelli, R.; Charbon, E.; Iacobucci, G.; Nessi, M.; Paolozzi, L.
Abstract: A 33.6 ps LSB Time-to-Digital converter was designed in 130 nm BiCMOS technology. The core of the converter is a differential 9-stage ring oscillator, based on a multi-path architecture. A novel version of this design is proposed, along with an analytical model of linearity. The model allowed us to understand the source of the performance superiority (in terms of linearity) of our design and to predict further improvements. The oscillator is integrated in a event-by-event self-calibration system that allows avoiding any PLL-based synchronization. For this reason and for the compactness and simplicity of the architecture, the proposed TDC is suitable for applications in which a large number of converters and a massive parallelization are required such as High-Energy Physics and medical imaging detector systems. A test chip for the TDC has been fabricated and tested. The TDC shows a DNL≤1.3 LSB, an INL≤2 LSB and a single-shot precision of 19.5 ps (0.58 LSB). The chip dissipates a power of 5.4 mW overall.